Blood Pressure Percentiles in Turkish Children and Adolescents - Ahmet Keskinoğlu; Pembe Keskinoglu; Su Özgür; Timur Köse (Galenos Yayinevi, 2020)
Aim:Pediatric hypertension, a public health concern, is now commonly known worldwide to be an early risk factor for cardiovascular and renal morbidity and mortality. Early detection of hypertension is of the utmost importance to help reduce serious complications. Several distributions of country-specific blood pressure (BP) percentiles have been established worldwide. The aim of this study is to determine BP percentiles in healthy Turkish children aged 2 to 18 years.Materials and Methods:In this cross-sectional study, BP was measured in 4,984 randomly selected children and adolescents aged 2-17 years. The 50th, 90th and 95th percentile of BP percentiles were determined for gender, age and height with the use a polynomial regression model. BP percentiles at median height were compared with the US Fourth Report references.Results:The normative values of systolic blood pressure (SBP) and diastolic blood pressure (DBP) increased with age for both genders and varied by gender. At median height, the age-specific differences at the 90th percentile of SBP tended to be higher in boys than in girls at all ages. DBP values in girls were higher than in boys until the age of 9 years, after which boys demonstrated higher values compared to girls.Conclusion:The age and height specific reference BP values determined in this study is a novel reference for Turkish children and adolescents. Turkish BP values are lower than existing US reference values.